Students’ Social and Psychological Adjustment to Studying at the Pedagogical University - Ольга Ю. Муллер; Наталья А. Ротова (Rossijskij psihologičeskij žurnal., 2020)
Introduction. This paper presents the results of the ascertaining stage of the experimental study and aims to identify the level of first-year students’ adjustment to studying at the pedagogical university and the characteristics of successful social-psychological adjustment among first-year students studying at the pedagogical university. The authors identified the components of social-psychological adjustment (success in educational activities, success in communication) and the criteria for assessing the level of adjustment in first-year students, including their awareness of the new role of a student, a future teacher (manifests itself through educational performance) and interaction with fellow students and teachers (manifests itself through a student’s individual behavioral style, the ability to express his/her opinion and take into account the opinions of others; the ability to support views and interests of his/her fellow students). Theoretical Basis. The article presents a retrospective view of the phenomenon of adjustment, a comparative analysis of theoretical views on understanding the essence of the concept of ‘adjustment’. This study is the first to clarify the concept of social and psychological adjustment among students of the pedagogical university, taking into account the process of communication of first-year students with their teachers and fellow students and the presence of a future teacher’s individual behavioral style. Results. The findings indicate the presence of high and average levels of adjustment to studying at the pedagogical university among first-year students, which enabled authors to formulate recommendations for organizing educational activities with first-year students at the pedagogical university to more rapidly coordinate their behavior in accordance with the requirements of the university. Discussion. First-year students showed a high level of adjustment to the educational group and an average level of adjustment to educational activities. Consequently, in order to overcome difficulties in mastering certain academic disciplines, the educational environment should be favorable for self-evaluation of educational performance, asking questions for introspection, and developing the ability to self-organize individual activities. Conclusion. The findings of this study are of direct practical relevance in the work of teachers with first-year students and may help choose the most effective forms of work, including interactive ones, contributing to successful adjustment to educational activities.